2022
DOI: 10.1016/j.msard.2021.103335
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection and hospitalization rate in Iranian multiple sclerosis patients: What we know by May 2021

Abstract: Background : Despite investigations on the effect of disease modifying therapies (DMTs) used in multiple sclerosis (MS) on coronavirus disease 2019 (COVID-19); there are still controversies. Objective : We designed this study to evaluate the epidemiological features of covid-19 in a large sample of people with MS (pwMS) in Isfahan, Iran, as well as the association between DMTs, risk of COVID-19 infection and hospitalization. Methods : In an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…We revealed that the prevalence of COVID-19 in the patients with MS was approximately 35%, but Naghavi et al indicated that the suspected rate of COVID-19 in the patients with MS was 20.4%, with 11.7% having PCR confirmation [ 21 ], and Zabalza et al reported that COVID-19 was prevalent in 6.3 percent of the patients with MS. The difference between these studies and our study could be due to genetic and racial differences, disease-modifying therapies, and poor compliance with COVID-19 protection protocols [ 22 26 ].…”
Section: Discussionmentioning
confidence: 90%
“…We revealed that the prevalence of COVID-19 in the patients with MS was approximately 35%, but Naghavi et al indicated that the suspected rate of COVID-19 in the patients with MS was 20.4%, with 11.7% having PCR confirmation [ 21 ], and Zabalza et al reported that COVID-19 was prevalent in 6.3 percent of the patients with MS. The difference between these studies and our study could be due to genetic and racial differences, disease-modifying therapies, and poor compliance with COVID-19 protection protocols [ 22 26 ].…”
Section: Discussionmentioning
confidence: 90%
“…The crude death rate in our study, 0.87%, is among the lowest reported for MS cohorts [1-6, 9-12, 17, 18, 8, 20, 22, 24, 25, 37, 44, 45]. This may be due to the fact that we excluded untreated patients, who tend to be older, more disabled, and to have a higher number of comorbidities and more frequently developed severe disease [5,16,23]. Another possible reason may be related to anti-CD20 dosing adjustments implemented in our clinic at the onset of the pandemic.…”
Section: Discussionmentioning
confidence: 63%
“…A sensitivity analysis was conducted for "laboratory-confirmed COVID-19" cases only. Fumarates were used as a reference group, similar to prior studies, because fumarates have not been identified to impart an increased risk of infection and are frequently used in clinical practice [29,30,18,16].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the immunosuppressive effect of high efficacy therapy, such as ocrelizumab, cladribine, and alemtuzumab, is believed to alter lymphocytes' proliferation and function, increasing the risk of infections. Recent studies did not provide a conclusive evidence to implicate a severe COVID-19 infection in patients receiving such therapies ( Bsteh et al, 2021 , Willis and Robertson, 2020 , De Angelis et al, 2020 , Seferoglu et al, 2021 , Luna et al, 2020 , Carandini et al, 2020 , Naghavi et al, May 2021 ). The risk factors for severe COVID-19 in MS patients were not different from the general population ( Louapre et al, 2020 , Ghadiri et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%